2D and 3D Modelling Electrical Resistivity Tomography (ERT) of Landslide Sliding and Weak Bedding Plane Along Mountain Road North Bengkulu-Lebong, Indonesia - Supiyati Supiyati; Suhendra Suhendra; Jesika Erni Elfrita Sinaga; Darmawan Ikhlas Fadli; Halauddin Halauddin (Department of Geography Education, University of Jember, 2024)
The North Bengkulu-Lebong Mountain Road is prone to landslide disasters due to its geological susceptibility to land movement. This study aims to measure and assess the sliding plane on the mountain road, particularly in the layer with a soft rock structure, such as clay rock. The study utilizes 2D and 3D Electrical Resistivity Tomography (ERT) methods with the Wenner-Schlumberger configuration to measure the resistivity of the rock layers.The research includes one 2D measurement point and one 3D ERT measurement point, estimating actual resistivity values in each rock layer. Our results identify triggering and controlling factors for landslide disasters in the research area. The geological conditions consist of layers of clay (200-500 Î©m), wet clay (500-900 Î©m), dry clay (1000-3000 Î©m), weathering clay (500-1000 Î©m), aquifer (10-65 Î©m), perched aquifer (100-200 Î©m), weathering igneous rock (>10000 Î©m), and massive intrusive rock (>20000 Î©m). These geological conditions significantly influence the strength of landslide materials, with the sliding of the soft rock layer causing landslides and resulting in a large volume of landslide material. Other contributing factors to landslides in this location include slope, topography, and hydrology, with extreme slopes ranging from 33Â° to 55Â°, making it a very steep area with high potential for landslides.